Generalized neighbor-interaction models induced by nonlinear lattices - Abdullaev, F. Kh. [UNESP]; Bludov, Yu. V.; Dmitriev, S. V.; Kevrekidis, P. G.; Konotop, V. V. (Amer Physical Soc, 2008)
It is shown that the tight-binding approximation of the nonlinear Schrodinger equation with a periodic linear potential and periodic in space nonlinearity coefficient gives rise to a number of nonlinear lattices with complex, both linear and nonlinear, neighbor interactions. The obtained lattices present nonstandard possibilities, among which we mention a quasilinear regime, where the pulse dynamics obeys essentially the linear Schrodinger equation. We analyze the properties of such models both in connection to their modulational stability, as well as in regard to the existence and stability of their localized solitary wave solutions.